2016
DOI: 10.1177/0739456x16659763
|View full text |Cite
|
Sign up to set email alerts
|

Creating and Preserving Affordable Homeownership Opportunities: Does Inclusionary Zoning Make Sense?

Abstract: This paper draws on data from the Montgomery County, Maryland, Moderately Priced Dwelling Unit (MPDU) program to analyze the effectiveness of inclusionary zoning as an affordable homeownership strategy. We find that the MPDU program has successfully produced a large number of affordable homeownership units since the program’s inception, particularly condominium and townhome units located in areas where new residential construction has occurred. While MPDU homes did not appreciate as rapidly as other market-rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 10 publications
(12 reference statements)
0
13
0
Order By: Relevance
“…The challenge of recruiting and retaining necessary workforces, in particular, has led some affluent areas to recognize the need for inclusion of diverse class groups (Lazarovic et al., 2016). To facilitate more diverse housing options within cities and suburbs, local governments are reversing planning practices that foster exclusivity by eliminating single‐family zoning or replacing some elements of exclusionary zoning with inclusionary zoning (also called inclusionary housing; Anacker, 2020; Dawkins et al., 2017; Kuhlmann, 2021). Importantly, research indicates that when affluent communities are compelled to require affordable housing, the implications for local quality of life and place status are relatively minimal (Eligon, 2020; Massey et al., 2013).…”
Section: Additional Class Nuances and Complicationsmentioning
confidence: 99%
“…The challenge of recruiting and retaining necessary workforces, in particular, has led some affluent areas to recognize the need for inclusion of diverse class groups (Lazarovic et al., 2016). To facilitate more diverse housing options within cities and suburbs, local governments are reversing planning practices that foster exclusivity by eliminating single‐family zoning or replacing some elements of exclusionary zoning with inclusionary zoning (also called inclusionary housing; Anacker, 2020; Dawkins et al., 2017; Kuhlmann, 2021). Importantly, research indicates that when affluent communities are compelled to require affordable housing, the implications for local quality of life and place status are relatively minimal (Eligon, 2020; Massey et al., 2013).…”
Section: Additional Class Nuances and Complicationsmentioning
confidence: 99%
“…Research has demonstrated the effectiveness of inclusionary zoning in increasing the supply of affordable housing (e.g. Crook et al, 2006;Been et al, 2007;Whitehead, 2007;Dawkins et al, 2017).…”
Section: Housing Criteria: the Inclusionary Zoning Techniquementioning
confidence: 99%
“…Studies have documented the negative effects of restraining affordable housing development, including racial and income segregation, job-housing imbalance, and traffic congestion (Anacker, 2020;Brown, 2001;Ellickson, 1981;Jacobus, 2015). Because the creation of inclusionary units typically ties to newly constructed developments, IH is more likely to be adopted in affluent suburban communities with relatively low base zoning and vibrant housing markets characterized by high housing prices and/or high housing price growth (Anacker, 2020;Dawkins et al, 2017;Schwartz, 2014).…”
Section: Local Influencesmentioning
confidence: 99%